Genome-wide and protein kinase-focused RNAi screens reveal conserved and novel damage response pathways in Trypanosoma brucei. - Jennifer A Stortz; Tiago D Serafim; Sam Alsford; Jonathan Wilkes; Fernando Fernandez-Cortes; Graham Hamilton; Emma Briggs; Leandro Lemgruber; David Horn; Jeremy C Mottram; Richard McCulloch (PLoS Pathogens)
All cells are subject to structural damage that must be addressed for continued growth. A wide range of damage affects the genome, meaning multiple pathways have evolved to repair or bypass the resulting DNA lesions. Though many repair pathways are conserved, their presence or function can reflect the life style of individual organisms. To identify genome maintenance pathways in a divergent eukaryote and important parasite, Trypanosoma brucei, we performed RNAi screens to identify genes important for survival following exposure to the alkylating agent methyl methanesulphonate. Amongst a cohort of broadly conserved and, therefore, early evolved repair pathways, we reveal multiple activities not so far examined functionally in T. brucei, including DNA polymerases, DNA helicases and chromatin factors. In addition, the screens reveal Trypanosoma- or kinetoplastid-specific repair-associated activities. We also provide focused analyses of repair-associated protein kinases and show that loss of at least nine, and potentially as many as 30 protein kinases, including a nuclear aurora kinase, sensitises T. brucei to alkylation damage. Our results demonstrate the potential for synthetic lethal genome-wide screening of gene function in T. brucei and provide an evolutionary perspective on the repair pathways that underpin effective responses to damage, with particular relevance for related kinetoplastid pathogens. By revealing that a large number of diverse T. brucei protein kinases act in the response to damage, we expand the range of eukaryotic signalling factors implicated in genome maintenance activities.